Influence of ethanol-biodiesel blends on diesel engines combustion behavior and particulate matter physicochemical characteristics - Preechar Karin; Aphichai Tripatara; Phyo Wai; Ban-seok Oh; Chinda Charoenphonphanich; Nuwong Chollacoop; Hidenori Kosaka (Case Studies in Chemical and Environmental Engineering, 2022)
Ethanol-blended biodiesel fuel can reduce smoke emissions by over 50% on both a single-cylinder engine and a four-cylinder engine. The average single primary particle size of biodiesel blended diesel, biodiesel, and ethanol blended biodiesel soot are approximately 30, 27, and 29 nm, respectively. The maximum graphene fringe length of biodiesel blended diesel, biodiesel, and ethanol blended biodiesel CI engine's soot are approximately 5.2, 4.6, and 4.5 nm. The carbon atom density of soot particles emitted from the diesel, biodiesel, and ethanol blended biodiesel CI engines are approximately 102, 91, and 88 atoms/nm3.
Keywords: Advanced Combustion Engine Technologies; Biodiesel Production and Applications; Catalytic Processes in Materials Science